Transição do Ensino Superior para o mercado de trabalho: uma comparação entre bacharéis e tecnólogos no Brasil do século XXI - Matheus Faleiros Silva (2018)
Higher Education is a fundamental institution in contemporary society. Understood as one of the pillars for a society based on more meritocratic and less hereditary criteria, tertiary education did not escape a stratification within it, with the expansion of access to that level in the 20th century. This differentiation was fundamental between institutions and courses more traditional as opposed to more vocational, responsible for the opening and democratization of higher education in the world. The present thesis proposes to rescue this discussion about the expansion and differentiation of higher education, as well as to bring two empirical studies in the Brazilian labor market comparing the graduates of the baccalaureate and technological undergraduate courses, an academic degree that has grown in recent years in Brazil. These studies are based on data from PNAD 2007, the only one with a supplement on professional education in Brazil, and RAIS from 2010 to 2015 that allows us to observe the trajectory of the two groups in the formal labor market in recent years.